Amphoteric metaanion chloride-free rosin size, raw material composition thereof, preparation method and application of amphoteric metaanion chloride-free rosin size

By using amphoteric anionic chlorine-free rosin collagen raw material composition and phase-transforming preparation technology, the problem of harmful chlorine compounds and anionic rosin gum in existing rosin gums is solved, and the rosin gum with good stability is achieved. It is suitable for neutral glue in the paper industry and improves the water resistance of paper.

CN119615668APending Publication Date: 2025-03-14JINING MING SHENG NEW MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411731090.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing rosin gums contain harmful chlorine compounds, and anionic rosin gums are highly dependent on aluminum sulfate and have limited application.

Method used

The amphoteric anionic chlorine-free rosin collagen raw material composition, including rosin, modifier, anionic starch emulsifier and amphoteric emulsifier, is prepared by the phase-transformation method in the preparation method, and the use of chlorine compounds is avoided.

Benefits of technology

The amphoteric anionic chlorine-free rosin glue with good chemical stability, mechanical stability and storage stability is achieved. It can be applied in the acid to neutral range. It is suitable for the paper industry and improves the water resistance of paper.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005160286940000021
    Figure BDA0005160286940000021
  • Figure BDA0005160286940000061
    Figure BDA0005160286940000061
  • Figure BDA0005160286940000081
    Figure BDA0005160286940000081
Patent Text Reader

Abstract

The invention provides an amphoteric metaanion chlorine-free rosin size raw material composition which comprises the following raw materials in parts by weight: 100-200 parts of rosin, 5-20 parts of a modifier, 5-8 parts of an anionic starch emulsifier, 5-8 parts of an amphoteric emulsifier and / or a proper amount of a functional aid, and the anionic starch emulsifier is an esterification cross-linked product of 1, 2, 3, 4-butanetetracarboxylic acid and starch. The preparation method of the amphoteric metaanion chlorine-free rosin size from the raw material composition comprises the following steps: heating and melting rosin, adding a modifier, reacting to obtain modified rosin, heating an anionic starch emulsifier and an amphoteric emulsifier to 60-90 DEG C, sequentially dropwise adding the materials into the modified rosin in a molten state, pre-emulsifying, and cooling to room temperature to obtain the amphoteric metaanion chlorine-free rosin size. And adding hot water into the pre-emulsified rosin liquid for phase inversion, cooling, and adding a functional auxiliary agent. The main raw materials of the amphoteric partial anion chlorine-free rosin size are natural renewable substances, the particle size distribution is narrow, the stability is good, the foam is less, fiber flocculation is not caused, and when the amphoteric partial anion chlorine-free rosin size is applied to papermaking sizing, acidic to neutral sizing can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of papermaking sizing agents, in particular to an amphoteric chlorine-free rosin glue. Background Art

[0002] Sizing is an important process in papermaking. Among the numerous paper sizing agents, rosin sizing agents are dominant, accounting for more than 2 / 3 of the total sizing amount. Rosin sizing agents include saponified rosin sizing, reinforced rosin sizing and dispersed rosin sizing. The sizing rate of dispersed rosin sizing is 4 times that of saponified rosin sizing and 2 times that of reinforced rosin sizing. Dispersed rosin sizing can improve the quality of paper and reduce the amount of aluminum sulfate and brightener.

[0003] Traditional rosin glue is anionic or cationic rosin glue. Cationic rosin glue basically contains 1,3-dichloro-2-propanol and 3-chloro-1,2-propanediol (hereinafter referred to as chloropropanol) or organic chlorine, which comes from the emulsifier using PAE or other chloride-containing cationic polymer monomers. The latest research has found that chloropropanol or organic chlorine is harmful to human health. Anionic rosin glue is highly dependent on aluminum sulfate and can only be used for acid sizing or other special sizing processes. It is incompatible with fillers such as calcium carbonate, and its application is limited. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a zwitterionic partial anion chlorine-free rosin glue, a raw material composition and a preparation method thereof, so as to solve the above-mentioned defects in the prior art.

[0005] The present invention is achieved by adopting the following technical solutions:

[0006] The first aspect of the present invention is to provide a zwitterionic partial anionic chlorine-free rosin glue raw material composition, which comprises the following raw materials in parts by weight: 100-200 parts of rosin, 5-20 parts of modifier, 5-8 parts of anionic starch emulsifier, 5-8 parts of amphoteric emulsifier, and / or an appropriate amount of functional additives, wherein the anionic starch emulsifier is an esterification cross-linking product of 1,2,3,4-butanetetracarboxylic acid (CAS: 1703-58-8, with a structural formula as shown in Formula I) and starch.

[0007] The anionic starch emulsifier is specifically prepared by the following method: 2-3 parts of 1,2,3,4-butanetetracarboxylic acid, 100-200 parts of starch, 1-2 parts of sodium hypophosphite, and 200-300 parts of water are heated to 45-55° C., stirred for reaction for 5-7 hours, and then 2.5-5.5 parts of sodium hydroxide solution are added dropwise to obtain the anionic starch emulsifier.

[0008]

[0009] The amphoteric emulsifier is selected from at least one of cocamidopropyl betaine and alkyl betaine.

[0010] The starch may be any type of starch commonly used in the art, including but not limited to corn starch, tapioca starch, potato starch, and wheat starch, preferably tapioca starch.

[0011] The modifier is selected from at least one of butenedioic acid, maleic acid and maleic anhydride.

[0012] The functional additives mainly play the role of defoaming and sterilizing for rosin glue, including defoamers, bactericides, etc. The functional additives can be added alone, or multiple functional additives can be added at the same time, and can be selected according to the actual dispersion and foaming of rosin glue and the needs of the application scenario. The amount of functional additives added is not particularly limited, and the amount that can achieve the corresponding function and does not affect the emulsification effect and stability of rosin glue is appropriate.

[0013] Furthermore, the defoamer is selected from at least one of emulsified silicone oil, high alcohol complex, polyether, and polydimethylsiloxane. Preferably, the defoamer is used in an amount of 1-3 parts by weight.

[0014] Furthermore, the fungicide is selected from at least one of Bit, MIT and CMIT. Preferably, the weight amount of the fungicide is 1-2 parts.

[0015] The second aspect of the present invention is to provide a method for preparing amphoteric partial anionic chlorine-free rosin glue, using the above-mentioned amphoteric partial anionic chlorine-free rosin glue raw material composition, specifically comprising the following steps:

[0016] S1, heating and melting rosin, adding a modifier and reacting the mixture sufficiently to obtain modified rosin;

[0017] S2, heating anionic starch emulsifier and amphoteric emulsifier to 60-90° C., and successively dropping them into the molten modified rosin for pre-emulsification to obtain pre-emulsified rosin liquid;

[0018] S3, slowly dripping 85-95° C. hot water into the pre-emulsified rosin solution to perform phase inversion, cooling, and adding functional additives to obtain the amphoteric partial anionic chlorine-free rosin glue.

[0019] The inventor unexpectedly discovered that the amphoteric partial anionic chlorine-free rosin glue prepared by using the esterification cross-linked product of 1,2,3,4-butanetetracarboxylic acid and starch as an anionic starch emulsifier in combination with an amphoteric emulsifier has outstanding chemical stability, mechanical stability and storage stability. The specific reason is not very clear. The inventor speculates that it may be because the 1,2,3,4-butanetetracarboxylic acid molecule contains four carboxyl groups, which can form multiple and complex esterification cross-links with multiple alcohol hydroxyl groups in starch. The cross-linked morphology of the formed esterified starch product is very different from that of general esterified starch. The use of it as an emulsifier can unexpectedly improve the stability of rosin glue. Based on the above discovery, the inventor completed the present invention.

[0020] Preferably, in step S1, the reaction temperature of rosin and modifier is 180-200° C., and the reaction time is 1-3 h.

[0021] Preferably, in step S2, the dropping time of the anionic starch emulsifier and the amphoteric emulsifier is 5-20 min, and the shear rate is 800-1200 rpm.

[0022] Preferably, the amount of hot water added in step S3 is 100-200 parts by weight.

[0023] The third aspect of the present invention is to provide a zwitterionic partial anionic chlorine-free rosin glue prepared by the above method, which has a solid content of 30%-50%, a viscosity of 15-50mPa.s, a chemical stability of ≤40ppm, a mechanical stability of ≤60ppm, and a storage stability of ≥12 months.

[0024] The fourth aspect of the present invention is to provide the use of the above-mentioned amphoteric partial anionic chlorine-free rosin glue in papermaking sizing. The inventors have found that the amphoteric partial anionic chlorine-free rosin glue of the present invention is applied to papermaking sizing to give the paper better water resistance. The specific mechanism is not very clear. It is speculated that it may be that some uncross-linked carboxyl groups in the amphoteric partial anionic chlorine-free rosin glue of the present invention produce cross-linking with hydroxyl groups in paper fibers during sizing and drying, thereby improving water resistance.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The amphoteric partial anionic chlorine-free rosin glue was prepared by using homemade anionic starch emulsifier and amphoteric emulsifier through phase inversion method. The product has a narrow particle size distribution and good stability.

[0027] 2. The product is easy to disperse in cold water and can be more evenly dispersed in the slurry during the wet-end addition process, resulting in better sizing effect;

[0028] 3. The product does not contain organic chlorine substances such as chloropropanol;

[0029] 4. Low dependence on aluminum sulfate, acidic to neutral sizing can be achieved;

[0030] 5. The process is simple and does not rely on complex production equipment. DETAILED DESCRIPTION

[0031] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only used as examples, but are not used to limit the scope of the present invention. Those skilled in the art can think of other obvious variations. The basic principles of the present invention defined in the following description can be applied to other embodiments, variations, improvements, equivalent solutions, and other technical solutions that do not deviate from the spirit and scope of the present invention.

[0032] The instruments or raw materials in the present invention that do not indicate the manufacturer are all conventional commercial instruments or raw materials. If the detection indicators involved in the embodiments of the present invention are not mentioned, they are all detected by conventional detection methods in the field. Among them:

[0033] 1. Solid content determination: 2g sample, drying at 150℃ for 30min;

[0034] 2. Viscosity measurement: rotational viscometer;

[0035] 3. Particle size determination: Malvern particle size analyzer;

[0036] 4. Chemical stability determination: Take 100g sample, add 10g 0.5mol / L calcium chloride, stir for 10min, and detect the residue on the 325-mesh filter;

[0037] 5. Mechanical stability determination: Take 100g sample, stir at 5000rpm for 30min, and detect the residue on the 325-mesh filter;

[0038] 6. Storage stability determination: Place at room temperature and observe the stratification.

[0039] Example 1

[0040] (1) Preparation of anionic starch emulsifier: 2 g of 1,2,3,4-butanetetracarboxylic acid, 100 g of cassava starch, 1 g of sodium hypophosphite, and 100 g of water were heated to 50° C., stirred for reaction for 6 h, and then 10 g of sodium hydroxide solution (concentration 32%) was added dropwise to obtain anionic starch emulsifier;

[0041] (2) Rosin modification: Weigh 200 g of rosin, heat it to 170 °C, add 20 g of maleic anhydride, and modify it at 180 °C for 2 h;

[0042] (3) Pre-emulsification: 8 g of cocamidopropyl betaine and 15 g of anionic starch emulsifier were heated to 60° C. and slowly added to the molten modified rosin over a period of 10 min. The mixture was fully pre-emulsified under stirring at 800 rpm.

[0043] (4) Phase transition: 200 g of water at 90° C. was slowly dripped into the pre-emulsified rosin solution. As the hot water was added, the viscosity of the pre-emulsion decreased rapidly from a maximum value, and the oil-in-water emulsion was transformed into an anionic rosin glue emulsion of oil-in-water. The pre-emulsion was cooled, 1 g of emulsified silicone oil defoamer was added, and water was added to adjust the solid content to obtain an amphoteric partial anionic chlorine-free rosin glue with a solid content of 40% and a viscosity of 20 mPa.s.

[0044] Example 2

[0045] (1) Preparation of anionic starch emulsifier: 3 g of 1,2,3,4-butanetetracarboxylic acid, 100 g of cassava starch, 2 g of sodium hypophosphite, and 200 g of water were heated to 50° C., stirred for reaction for 6 h, and then 16 g of sodium hydroxide solution (concentration 32%) was added dropwise to obtain anionic starch emulsifier;

[0046] (2) Rosin modification: Weigh 200 g of rosin, heat it to 180 °C, add 20 g of fumaric acid, and modify it at 200 °C for 2 h;

[0047] (3) Pre-emulsification: 15 g of alkyl betaine and 8 g of anionic starch emulsifier were heated to 60° C. and slowly added to the molten modified rosin over a period of 10 min. The mixture was fully pre-emulsified under stirring at 1200 rpm.

[0048] (4) Phase inversion: 200 g of water at 90° C. was slowly dripped into the pre-emulsified rosin solution. As the hot water was added, the viscosity of the pre-emulsion decreased rapidly from a maximum value, and the oil-in-water emulsion was converted into an anionic rosin glue emulsion of oil-in-water. The pre-emulsion was cooled, and 2 g of polydimethylsiloxane defoamer was added. Water was added to adjust the solid content to obtain amphoteric partial anionic chlorine-free rosin glue with a solid content of 40% and a viscosity of 20 mPa.s.

[0049] Example 3

[0050] (1) Preparation of anionic starch emulsifier: 3 g of 1,2,3,4-butanetetracarboxylic acid, 200 g of cassava starch, 2 g of sodium hypophosphite, and 200 g of water were heated to 50° C., stirred for reaction for 6 h, and then 8 g of sodium hydroxide solution (concentration 32%) was added dropwise to obtain anionic starch emulsifier;

[0051] (2) Rosin modification: Weigh 100 g of rosin, heat it to 170 °C, add 5 g of maleic anhydride, and modify it at 180 °C for 2 h;

[0052] (3) Pre-emulsification: 15 g of alkyl betaine and 15 g of anionic starch emulsifier were heated to 60° C. and slowly added to the molten modified rosin over a period of 10 min. The mixture was fully pre-emulsified under stirring at 1200 rpm.

[0053] (4) Phase inversion: 100 g of water at a temperature of 90-95° C. is slowly dripped into the pre-emulsified rosin solution. As the hot water is added, the viscosity of the pre-emulsion decreases rapidly from a maximum value, and the oil-in-water emulsion is converted into an anionic rosin glue emulsion of oil-in-water. The pre-emulsion is cooled, and 0.5 g of a higher alcohol defoamer is added. Water is added to adjust the solid content to obtain an amphoteric partial anionic chlorine-free rosin glue with a solid content of 30% and a viscosity of 10 mPa.s.

[0054] Example 4

[0055] (1) Preparation of anionic starch emulsifier: 3 g of 1,2,3,4-butanetetracarboxylic acid, 200 g of cassava starch, 2 g of sodium hypophosphite, and 200 g of water were heated to 50° C., stirred for reaction for 6 h, and then 8 g of sodium hydroxide solution (concentration 32%) was added dropwise to obtain anionic starch emulsifier;

[0056] (2) Rosin modification: Weigh 200 g of rosin, heat it to 170 °C, add 20 g of maleic anhydride, and modify it at 200 °C for 2 h;

[0057] (3) Pre-emulsification: Heat 15 g of cocamidopropyl betaine and 15 g of anionic starch emulsifier to 60° C., slowly add them to the molten modified rosin, add them over 10 min, and fully pre-emulsify them under stirring at 800 rpm;

[0058] (4) Phase inversion: 150 g of water at a temperature of 90-95° C. is slowly dripped into the pre-emulsified rosin solution. As the hot water is added, the viscosity of the pre-emulsion decreases rapidly from a maximum value, and the oil-in-water emulsion is converted into an anionic rosin glue emulsion of oil-in-water. The pre-emulsion is cooled, 0.5 g of a polyether defoamer is added, and water is added to adjust the solid content to obtain an amphoteric partial anionic chlorine-free rosin glue with a solid content of 50% and a viscosity of 17 mPa.s.

[0059] Comparative Example 1

[0060] The commercially available rosin glue is model NS-801 produced by Arakawa Chemical Industries, Ltd. of Japan.

[0061] Comparative Example 2

[0062] Triacylglycerol (also known as 1,2,3-propanetricarboxylic acid, CAS: 99-14-9, structural formula as shown in Formula II) is used to replace the 1,2,3,4-butanetetracarboxylic acid in Example 4, and the rest is the same as in Example 4. The specific process is as follows:

[0063]

[0064] (1) Preparation of anionic starch emulsifier: 3 g of triacylglycerol, 200 g of cassava starch, 2 g of sodium hypophosphite, and 200 g of water were heated to 50° C., stirred for reaction for 6 h, and then 8 g of sodium hydroxide solution (concentration 32%) was added dropwise to obtain anionic starch emulsifier;

[0065] (2) Rosin modification: Weigh 200 g of rosin, heat it to 170 °C, add 20 g of maleic anhydride, and modify it at 200 °C for 2 h;

[0066] (3) Pre-emulsification: Heat 15 g of cocamidopropyl betaine and 15 g of anionic starch emulsifier to 60° C., slowly add them to the molten modified rosin, add them over 10 min, and fully pre-emulsify them under stirring at 800 rpm;

[0067] (4) Phase inversion: 150 g of water at a temperature of 90-95° C. is slowly dripped into the pre-emulsified rosin solution. As the hot water is added, the viscosity of the pre-emulsion decreases rapidly from a maximum value, and the oil-in-water emulsion is converted into an anionic rosin glue emulsion of oil-in-water. The pre-emulsion is cooled, 0.5 g of a polyether defoamer is added, and water is added to adjust the solid content to obtain an amphoteric partial anionic chlorine-free rosin glue with a solid content of 50% and a viscosity of 17 mPa.s.

[0068] The indicators and properties of the anionic rosin glue of the above-mentioned embodiments and comparative examples were measured, and the results are shown in Table 1.

[0069] Table 1 Rosin glue performance index

[0070] sample Particle size / um Chemical stability / ppm Mechanical stability / ppm Stability / month Example 1 0.35 27 35 12 Example 2 0.35 21 57 12 Example 3 0.33 38 53 12 Example 4 0.27 15 28 12 Comparative Example 1 0.63 86 147 6 Comparative Example 2 0.49 75 57 10

[0071] When Examples 1-4 were stored at 30°C for 12 months, the samples still maintained a uniform and stable emulsion state, while Comparative Example Sample 1 showed delamination and demulsification, and bottom precipitation after 6 months, and Comparative Example 2 showed delamination and demulsification, and bottom precipitation after 10 months. From the test results, it can be seen that the chemical stability and mechanical stability of the amphoteric partial anionic chlorine-free rosin glue of the present invention are better than those of the comparative examples, and the storage stability reaches 12 months, which is significantly better than the comparative samples, indicating that the emulsifier used in the present invention has a better effect of stabilizing the rosin glue.

[0072] Application Examples

[0073] Experimental plan: Design and manufacture a paper with a basis weight of 100g / m 2 .

[0074] Process: pulp 85% + rosin glue + talcum powder 15% + CPAM (200ppm).

[0075] Rosin glue addition amount: 14kg / t paper, 18kg / t paper (wet / dry, each sample is added at 35% solid content).

[0076] According to the above process, the pH value of the blank paper pulp was adjusted to about 6.0-7.0 with a dissolved 30% citric acid solution, and then the rosin glue prepared in Example 1-4 or Comparative Example 1-2 was added, and talcum powder was added after stirring for 1 minute, and a retention agent was added after stirring for 1 minute. After 1 minute, the prepared pulp was removed, and sheets were made with a 73-62 semi-automatic paper sheet former, and pressed with a 73-50 standard paper sheet press, and then dried with a glazing machine. The 1-minute Cobb water absorption value of the paper sample was tested, and the average value was taken after three parallel tests. The specific test results are shown in Table 2.

[0077] Table 2 Rosin glue application performance indicators

[0078]

[0079] The main raw materials used in the raw material composition of the amphoteric partial anionic chlorine-free rosin glue of the present invention are all natural renewable materials, which are environmentally friendly and easy to degrade, with simple process, low cost and convenient use. The amphoteric partial anionic chlorine-free rosin glue is prepared by a phase inversion method using a homemade anionic starch emulsifier, has a narrow particle size distribution, good stability, is easily dispersed in cold water, is simple to operate, and does not require readjustment of the original process; has a high free rosin content, low viscosity, high whiteness, stable quality, and can be placed for a long time, and has a quality shelf life of 12 months at room temperature. The amphoteric partial anionic chlorine-free rosin glue has less foam, does not cause fiber flocculation, and does not affect paper material forming.

[0080] In summary, the amphoteric partial anionic chlorine-free rosin glue of the present invention has the advantages of reduced cost, convenient use, good stability, less foam and strong adaptability, etc., can achieve acidic to neutral sizing, and its preparation process is simple and has low requirements on equipment. When sizing, conventional retention system and sizing process are used, which can achieve the purpose of neutral sizing.

[0081] It should be understood by those skilled in the art that the above embodiments are only examples and do not limit the present invention. The purpose of the present invention has been fully and effectively achieved. The functional and structural principles of the present invention have been demonstrated and explained in the embodiments, and the embodiments of the present invention may be deformed or modified in any way without departing from the principles.

Claims

1. A zwitterionic partial anion chlorine-free rosin glue raw material composition, characterized in that: The invention comprises the following raw materials in parts by weight: 100-200 parts of rosin, 5-20 parts of modifier, 5-8 parts of anionic starch emulsifier, 5-8 parts of amphoteric emulsifier, and / or an appropriate amount of functional additives, wherein the anionic starch emulsifier is an esterification cross-linking product of 1,2,3,4-butanetetracarboxylic acid and starch.

2. The amphoteric partial anion chlorine-free rosin glue raw material composition according to claim 1, characterized in that: The anionic starch emulsifier is prepared by the following method: 2-3 parts of 1,2,3,4-butanetetracarboxylic acid, 100-200 parts of starch, 1-2 parts of sodium hypophosphite and 200-300 parts of water are heated to 45-55° C., stirred for reaction for 5-7 hours, and then 2.5-5.5 parts of sodium hydroxide solution are added dropwise to obtain the anionic starch emulsifier.

3. The amphoteric partial anion chlorine-free rosin glue raw material composition according to claim 1, characterized in that: The amphoteric emulsifier is selected from at least one of cocamidopropyl betaine and alkyl betaine.

4. The amphoteric partial anion chlorine-free rosin glue raw material composition according to claim 1, characterized in that: The modifier is selected from at least one of butenedioic acid, maleic acid and maleic anhydride.

5. The amphoteric partial anion chlorine-free rosin glue raw material composition according to claim 1, characterized in that: The functional auxiliary agent is a defoaming agent, which is specifically selected from at least one of emulsified silicone oil, a high-carbon alcohol complex, polyether, and polydimethylsiloxane.

6. The amphoteric partial anion chlorine-free rosin glue raw material composition according to claim 5, characterized in that: The weight dosage of the defoamer is 1-3 parts.

7. A method for preparing amphoteric partial anionic chlorine-free rosin glue, using the amphoteric partial anionic chlorine-free rosin glue raw material composition according to any one of claims 1 to 6, specifically comprising the following steps: S1, heating and melting rosin, adding a modifier and reacting the mixture sufficiently to obtain modified rosin; S2, heating anionic starch emulsifier and amphoteric emulsifier to 60-90° C., and successively dropping them into the molten modified rosin for pre-emulsification to obtain pre-emulsified rosin liquid; S3, slowly dripping 85-95° C. hot water into the pre-emulsified rosin solution to perform phase inversion, cooling, and adding functional additives to obtain the amphoteric partial anionic chlorine-free rosin glue.

8. The method according to claim 7, characterized in that In step S1, the reaction temperature of rosin and modifier is 180-200°C, and the reaction time is 1-3h; in step S2, the dropwise addition time of anionic starch emulsifier and amphoteric emulsifier is 5-20min, and the shear rate is 800-1200rpm; in step S3, the amount of hot water added is 100-200 parts by weight.

9. The amphoteric partial anion chlorine-free rosin glue prepared according to the method of claim 7 or 8, characterized in that: The solid content is 30%-50%, the viscosity is 15-50mPa.s, the chemical stability is ≤40ppm, the mechanical stability is ≤60ppm, and the storage stability is ≥12 months.

10. Use of the amphoteric partial anionic chlorine-free rosin glue according to claim 9 in papermaking sizing.

Citation Information

Patent Citations

  • High-performance cationic rosin size and preparation method thereof

    CN106317421A

  • Anionic rosin size and preparation method thereof

    CN117779517A

  • High content of 3-methylbutyl tetraisopentyl esters of butane tetracarboxylic acid

    EP4345128A1

  • Active sizing compositions

    GB8920456D0

  • Coating compositions containing starch half-esters and process for preparing same

    US4061610A